Preparation and characterization of Ag nanoparticles decorated with ZnO microstructures for the catalytic photodegradation of methylene blue dye under UV light irradiation (Penyediaan dan pencirian Ag berstruktur nanopartikel diubahsuai dengan ZnO berstruktur mikro untuk penurunan fotokatalisis pewarna metilena biru di bawah sinar UV) - Rafaie, Hartini Ahmad; Safian, Nur Azmina Mohamed; Nor, Roslan Md; Amin, Yusoff Mohd (Malaysian Analytical Sciences Society, 2018)
Ag nanoparticles (AgNPs) decorated with ZnO microstructures was prepared by sol-gel method at different Ag concentration. The structures, composition and morphology of the samples were characterized by X-ray diffraction (XRD), electron dispersive X-ray spectroscopy (EDS) and field emission scanning electron microscope (FESEM). FESEM images shows that the samples were composed of Ag and ZnO with the particles size ranging from 100 to 500 nm. EDS analysis confirmed that atomic % increases as higher molar concentration applied with value of 5.6 at.% and 16.1 at.% for sample 0.05M and 0.1M AgNPs decorated ZnO microstructures. Methylene blue (MB) dye was used as a representative of dye pollutant to conduct the catalytic photodegradation activity. The AgNPs decorated with ZnO particles exhibited a better photocatalytic activity than the pure ZnO particles. The results show that an increasing of photodegradation rate constant, k was obtained when higher concentration of Ag was applied to the ZnO with value of 0.016, 0.026 and 0.032 min-1 for pure ZnO, 0.05M AgZnO and 0.1M AgZnO nanoparticles, respectively. The increased of k value in the presence of Ag was due to the prolonged lifetime of the photogenerated electron hole pairs in ZnO as a result of Ag nanoparticles acting as electron sink.